La Joya Design: www.lajoyadesign.com - Briceño Guarachi, Luz (Base Diseño e Innovación, 2015)
La Joya Design is a fashion and textile company that was founded in Barcelona the year 2006 by the Chilean designer Luz Briceño. It has exported its collections to various countries in Europe such as Italy, France and Portugal. Luz Briceño also develops unique designs for brides and bridesmaids, or clothing to order in her home-workshop of El Arrayán, in Santiago. In 2011, the designer founded the first Gremial Association of Fashion Designers of Chile.